2023
DOI: 10.57235/jetish.v2i1.358
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Extrinsic Rewards on Work Motivation in the Apron Movement Control (AMC) Unit at Adi Soemarmo Boyolali International Airport

Abstract: This research is a qualitative research that aims to analyze extrinsic rewards on work motivation in the apron movement control unit at Adi Soemarmo Boyolali Airport. Extrinsic Rewards are tangible rewards that come from outside the person himself, can be financial, such as salaries, bonuses, benefits, and can be non-financial, such as promotions. Work motivation is a state or energy that drives employees who are ordered or given assignments to achieve organizational goals. (Apron Movement Control/AMC) is an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With these job demands, UPBU plays an important role in maintaining and improving the quality of work life (QWL) for its employees. QWL is an important aspect of the aviation industry because, in addition to reducing employee stress (Akinlade & Nwaodike, 2021;Sarabia-López et al, 2017), it can also increase motivation (Gautama et al, 2023;Setyowati & Syaputra, 2023), and support them in providing the best service to airport users (Hamzah et al, 2020). Research on the QWL in the airport environment is important because it can provide insights into ways to improve performance and operational efficiency and ensure public safety and satisfaction (Akinlade & Nwaodike, 2021;Allameh et al, 2013;Dhamodharan & Thiruvarangadas, 2022;Sarabia-López et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With these job demands, UPBU plays an important role in maintaining and improving the quality of work life (QWL) for its employees. QWL is an important aspect of the aviation industry because, in addition to reducing employee stress (Akinlade & Nwaodike, 2021;Sarabia-López et al, 2017), it can also increase motivation (Gautama et al, 2023;Setyowati & Syaputra, 2023), and support them in providing the best service to airport users (Hamzah et al, 2020). Research on the QWL in the airport environment is important because it can provide insights into ways to improve performance and operational efficiency and ensure public safety and satisfaction (Akinlade & Nwaodike, 2021;Allameh et al, 2013;Dhamodharan & Thiruvarangadas, 2022;Sarabia-López et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The study by Sarabia-López et al (2017) on air traffic controllers at an airport showed that the well-being achieved through work is the most dominant dimension followed by institutional support for work. The presence of compensation and rewards motivates the work of airport employees (Kasmawati et al, 2021;Setyowati & Syaputra, 2023). According to Kirschenbaum et al (2012), security decisions at airports often fail to follow established rules and procedures.…”
Section: Introductionmentioning
confidence: 99%